Mathematical Literacy Ability of Junior High School Students on the Material of Ranked Numbers and Root Forms - Adistiana Putri Rusyananda; Rita Pramujiyanti Khotimah (STAI Hubbulwathan Duri, 2023)
The purpose of this research is to provide a descriptive account of junior high school students' knowledge of mathematics, specifically their fluency with ranking numbers and root forms. A qualitative research approach with a descriptive focus is used in this study. Fifty-four students from Sidoharjo, Indonesia, a public junior high school, participated in the research. There were quizzes and interrogations to get information. Triangulation of methods was utilised to ensure the accuracy of the data collected. The analysis of data in this study consists of three parts: data reduction, data display, and conclusion drawing. There are no gaps in high school pupils' ability to read, write, and do computations at a proficient level. Students in this group can build mathematical models and comprehend mathematics, but they struggle with the second question's requirement that they use such models to describe, explain, or estimate a phenomenon or event. Students in the lowest ability level will only be able to answer the first question correctly if they use concepts, processes, and facts to describe, explain, or estimate a phenomenon or event.